Linearitas Wujud Tradisi Lisan terhadap Lagu Bedandeng Suku Kutai di Kecamatan Tenggarong - Kresna Syuhada Rawanggalih; Yofi Irvan Vivian; Zamrud Whidas Pratama (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2023)
Bedandeng is one of the traditional vocals found in the Kutai tribe in Tenggarong District and is sung while working (in the fields) and putting children to sleep. Currently, many young people from the Kutai tribe are not familiar with the Bedandeng song because it is rarely performed, so they do not know its musical characteristics and the context in which it is spoken. Bedandeng song research uses qualitative methods with a descriptive analysis approach to determine musical forms and (non-musical) speech contexts. There are four Bedandeng lyrics which adjust the function, place, and activities of the singer (wailing, advising, and putting the child to sleep). The four lyrics of Bedandeng have musical characteristics by Jean Ferris which include phrases (antecedents and consequents), melodies (C – D – Eb – F – G – Ab), themes (adjusting the place and activities of the singer), scale (C scale Original Minor), and uses melismatic and syllabic concepts in each of its lyrics. Context of speech is also found in Bedandeng's fourth lyrics, namely culture, situation, social, and ideology. The songs in the four Bedandeng lyrics have a linearity that is related to the musical characteristics and speech context (oral tradition) in the lyrics conveyed by the singer.